RED BOOK OF ESTONIAN PUBLICATIONS 1535–1850: EXPERIENCE AND LESSONS OF THE PROJECT - REIMO, TIIU; KONSA, KURMO (Knygotyra, 2011)
Preservation of objects that have social, scientific or cultural significance for the future has become one of the most challenging problems of the society. The establishment of preservation priorities is one of the most complicated tasks facing the information institutions. The whole procedure entails a lot of responsibility as decisions that are made will determine the amount of information available to future generations. The article demonstrates experience and lessons gained in the project “Red Book of Estonian Publications, 1535–1850” that was conducted in 2003–2006. Growing out from the need to make decisions for preservation strategies and to establish principles for future digitization of Estonian book heritage, the project drew attention to the importance of having distinct methodology and coherent criteria for the assessment of culturally valuable objects. The project team stressed the importance of preservation quality, especially when using reformatting technologies like microfilming and digitization. Preservation of informational integrity of a document is one of the key questions of the digital future.
Keywords: preservation; book heritage; red book; assessment of significance; informational integrity; preservation quality